KONTRIBUSI KECERDASAN EMOSIONAL TERHADAP INTERAKSI SOSIAL SISWA SMP - Saputri, Niken Dwi; Soeharto, Soeharto; Djannah, Wardatul (Universitas Sebelas Maret, 2016)
This study was aimed to know about: (1) the condition of social interaction of junior high school students, (2) the level of emotional intelligence of junior high school students, (3) the contribution of emotional intelligence towards social interaction of junior high school students. The method which used in this study was a descriptive correlational study. The population was 266 of eight grades students of junior high school students. The sample was 159 taken by simple random sampling technique. The instruments in collecting data were questionnaires of social interaction and questionnaires of emotional intelligence. The technique which used to analyze data was simple linier regression and analysis statistic. The result of this study showed that: (1) the condition of social interaction of junior high school students was average, that was 57,9 %, (2) the level of emotional intelligence of junior high school students was average, that was 62,9 %, and (3) the contribution of emotional intelligence towards social interaction of junior high school students was 49,1 %. Based on that result, it could be concluded that were an important role and contribution of emotional intelligence towards social interaction of eight grades of junior high school students. It was useful for students to optimize the ability of dealing with up and down of living towards the better life.Penelitian ini bertujuan untuk mengetahui: (1) kondisi interaksi sosial siswa. (2) tingkat kecerdasan emosional siswa SMP, (3) kontribusi kecerdasan emosional terhadap interaksi sosial siswa. Metode yang digunakan adalah deskriptif korelasional. Populasinya adalah 266 siswa SMP. Sampelnya adalah 159 siswa yang diambil dengan menggunakan teknik simple random sampling. Instrumen pengumpulan data menggunakan angket interaksi sosial dan angket kecerdasan emosional. Teknik analisis data menggunakan regresi linier sederhana dan analisis statistik. Hasil Penelitian menunjukkan bahwa: (1) interaksi sosial siswa kelas VIII tergolong sedang, yaitu 57,9 %, (2) tingkat kecerdasan emosional siswa kelas VIII tergolong sedang, yaitu 62,9 %, (3) kecerdasan emosional berkontribusi terhadap interaksi sosial siswa kelas VIII sebesar 49,1 %. Berdasarkan hasil tersebut, dapat ditarik kesimpulan bahwa adanya kecerdasan emosional memiliki peranan penting dan berkontribusi terhadap interaksi sosial siswa SMP. Hal ini berguna bagi siswa untuk mengoptimalkan kemampuannya dalam menghadapi lika-liku kehidupan untuk mencapai kehidupan yang lebih baik.